Effects of Chemopreventive Natural Compounds on the Accuracy of 8-oxo-7,8-dihydro-2′-deoxyguanosine Translesion Synthesis - Nachtergael, Amandine; Lanterbecq, Déborah; Spanoghe, Martin; Belayew, Alexandra; Duez, Pierre (Planta Medica, 2021)
Translesion synthesis is a DNA damage tolerance mechanism that relies on a series of specialized DNA polymerases able to bypass a lesion on a DNA template strand during replication or post-repair synthesis. Specialized translesion synthesis DNA polymerases pursue replication by inserting a base opposite to this lesion, correctly or incorrectly depending on the lesion nature, involved DNA polymerase(s), sequence context, and still unknown factors. To measure the correct or mutagenic outcome of 8-oxo-7,8-dihydro-2′-deoxyguanosine bypass by translesion synthesis, a primer-extension assay was performed in vitro on a template DNA bearing this lesion in the presence of nuclear proteins extracted from human intestinal epithelial cells (FHs 74 Int cell line); the reaction products were analyzed by both denaturing capillary electrophoresis (to measure the yield of translesion elongation) and pyrosequencing (to determine the identity of the nucleotide inserted in front of the lesion). The influence of 14 natural polyphenols on the correct or mutagenic outcome of translesion synthesis through 8-oxo-7,8-dihydro-2′-deoxyguanosine was then evaluated in 2 experimental conditions by adding the polyphenol either (i) to the reaction mix during the primer extension assay; or (ii) to the culture medium, 24 h before cell harvest and nuclear proteins extraction. Most of the tested polyphenols significantly influenced the outcome of translesion synthesis, either through an error-free (apigenin, baicalein, sakuranetin, and myricetin) or a mutagenic pathway (epicatechin, chalcone, genistein, magnolol, and honokiol).
Keywords: translesion synthesis; flavonoids; neolignans; mutation; primer extension assay